Evaluasi Tingkat Akurasi Digital Elevation Model (DEM) SRTM dan ASTER GDEM dalam Pemodelan Daerah Aliran Sungai (DAS) Ciliwung - Sutisna, Ade Suhendar; Putro, Haryono (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Availability of Digital Elevation Model (DEM) dataset and Geographic Information System (GIS), makes the watershed properties can be extracted automatically. There are two DEM providers which are freely accessible for research purposes and commonly use that is the Shuttle Radar Topographic Mission (SRTM) - DEM (30m) and Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model Version 2 (GDEM V2). Based on the result of modeling conducted at Ciliwung River Basin with Qgis application, area generated from SRTM data is 5% smaller than Ciliwung River Basin which obtained from BPDAS Ciliwung-Citarum as a reference, while the result of ASTER-GDEM data is 87% larger than reference. Linear Regression Test and t-Test performed on three segments of the watershed shows that the upstream of both samples gives a good accuracy result that is R2 = 0,999; P = 0,499 (SRTM) and R2 = 0,999; P = 0,481 (ASTER-GDEM), while in the middle and downstream segments respectively for both samples are SRTM with R2 = 0,993; P = 0,413 and R2 = 0,734; P = 0,088; and then ASTER-GDEM with R2 = 0,784; P = 0,00038 and R2 = 0,376; P = 1,27209 x10-22.